Varieties of trust in preschoolers’ learning and practical decisions - Pesch, Annelise; Koenig, Melissa A. (PLOS ONE, 2018)
Keeping commitments to others can be difficult, and we know that people sometimes fail to keep them. How does a speaker’s ability to keep commitments affect children’s practical decisions to trust and their epistemic decisions to learn? An amassing body of research documents children’s trust in testimonial learning decisions, which can be moved in the face of epistemic and moral evidence about an agent. However, other bases for trust go largely unexplored in this literature, such as interpersonal reasons to trust. Here, we investigated how direct bids for interpersonal trust in the form of making commitments, or obligations to the listener, influence a range of decisions toward that agent. We found that 3- and 4-year-olds’ (N = 75) practical decisions to wait and to share were moved as a function of a person’s commitment-keeping ability, but epistemic decisions to learn were not. Keeping one’s commitments may provide children with interpersonal reasons to trust, reasons that may function in ways distinct from the considerations that bear on accepting a claim.